Financial innovation of mass destruction: The story of a countrywide FX options debacle - Anna Sławik; Joanna Bohatkiewicz-Czaicka (Risks, 2022)
Astonishingly little attention has been paid in academic literature to the 2008-2009 foreign exchange (FX) options debacle in Poland, the scale of which was unheard of. It affected not only an individual organization but a significant part of economy, being an example of a situation in which operational risk at the company level could have impacted systemic risk. The research provides evidence of the dark side of financial innovations through an analysis of a countrywide case on an emerging market, utilizing a primary qualitative content analysis (QCA) of over 750 documents (including press releases, public authorities' accounts, and corporate statements). It documents that the FX options debacle was caused by financial institutions which shrouded some aspects of innovative securities or took advantage of information asymmetry to exploit uninformed clients. The study concludes that both adequate legal regulations and proper operational risk management are crucial to avoid similar corporate failures.
Keywords: 330; derivatives debacle; financial innovation; FX options